Study of Characteristics of The Conflict Between The Sumatera Elephant (Elephas maximus Sumatranus) with Communities around Tesso Nilo National Park, Riau - Arum, Rizki Sekar; Rizaldi, Rizaldi; Sunarto, Sunarto (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018)DO - 10.24843/metamorfosa.2018.v05.i02.p20, 2018)
Human-elephant conflict is one of main issues in wildlife conservation. The trigger of human-elephant conflict is forest convertion in Tesso Nilo National Park. A study about characteristic of human elephant conflict has been conducted from March until April 2016 in some area of the park including Lubuk Kembang Bunga and Air Hitam villages, Riau Province, Indonesia. This study aimed to describe the characteristics of dispute area have been and land use in the park. A survey and interview have been conducted to 30 local inhibitans. Lubuk Kembang Bunga and Air hitam villageswere located near by the elephant forest habitat (0-10 km) with elevation 0f 200-100 m above the sea level. The area mostly flat and close to rivers. The elephant attack palm oil and rubber plantation. Historical change of land use at Tesso Nilo National Park from 2004 to 2016 has proved to damaged the elephant habitat, while the elephants come to the plantation where they had ranged in the past time.